Pengelolaan Kegiatan Ekstrakurikuler PramukaDi SD Negeri 2 Ngarap-Arap Kabupaten GroboganTahun Pelajaran 2016/2017 - Budiyono, Eko; , Prof. Dr. Bambang SumardjokoM.Pd; , Dr. Achmad Fathoni, M.Pd (2017)
The purpose of this study is describe: 1) Tthe planning of extracurricular activities Scouting; 2) The implementation of extracurricular activities Scouting; 3) Tthe supervision of extracurricular activities Scouting; in SD Negeri 2 Ngarap-arap Grobogan. This research uses a qualitative research approach. Data was collected through interviews, observation, and documentation. The results showed: 1) The activities of planning extracurricular activities Scouts held at the beginning of the school year, starting with the preparation of the program, those involved in planning the program of extracurricular activities Scouting is a teacher as well Scoutmaster, Chairman of the Cluster front, and Kamabigus as well as the Principal, and People parents; 2) Extracurricular activities Scouts in SD Negeri 2 Ngarap-arap implemented since grade 1 to grade 6. The event consists of an exercise routine (weekly) and exploration. Exercise regularly held once a week; 3) Monitoring Scout extracurricular activities carried out as a means of quality assurance scouts extracurricular. The principal as Kamabigus act as a watchdog Internal became involved in the implementation of the extracurricular activity of Scouting. Keywords:planning, extracurricular scout